НОҚУЛАЙ ОБ-ҲАВО ШАРОИТИДА МАШҒУЛОТЛАРНИ ТАШКИЛ ҚИЛИШ ВА ЎТКАЗИШ МУАММОЛАРИ - Сейтмуратов, Т.Ш. (SCIENCE and SOCIETY, 2023)
According to the analysis of scientific sources relevant to this topic in the article, the rapid transition of physiological processes between internal and external body temperature, as well as in the process of blood supply to the body, positively affects its blood supply during muscle contraction and stretching.
Keywords: training; air temperature; environment; physiological process; competition; body; functional training